2016
DOI: 10.3758/s13421-016-0660-5
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the preparatory function of counterfactual thinking

Abstract: Why do individuals mentally modify reality (e.g., "If it hadn't rained, we would have won the game")? According to the dominant view, counterfactuals primarily serve to prepare future performance. In fact, individuals who have just failed a task tend to modify the uncontrollable features of their attempt (e.g., "If the rules of the game were different, I would have won it"), generating counterfactuals that are unlikely to play any preparatory role. By contrast, they generate prefactuals that focus on the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Intriguingly, in that same paper, a study of marathon runners reflecting on their performance revealed a very different rate of 68% of counterfactuals focusing on personally controllable actions. In a third paper by Mercier et al (2017), using laboratory tasks involving word search or syllogisms, the rate of counterfactuals that centered on controllable action hovered between 9% and 35%. An aspect of all three of these papers has been to benchmark the rate of controllable counterfactuals against the rate of controllable prefactuals (i.e., future-focused if-then contingencies, Epstude, Scholl, & Roese, 2016); the general finding was that the latter are more likely to focus on controllable actions than the former.…”
Section: Structural Envelope Of Counterfactual Thoughtsmentioning
confidence: 99%
“…Intriguingly, in that same paper, a study of marathon runners reflecting on their performance revealed a very different rate of 68% of counterfactuals focusing on personally controllable actions. In a third paper by Mercier et al (2017), using laboratory tasks involving word search or syllogisms, the rate of counterfactuals that centered on controllable action hovered between 9% and 35%. An aspect of all three of these papers has been to benchmark the rate of controllable counterfactuals against the rate of controllable prefactuals (i.e., future-focused if-then contingencies, Epstude, Scholl, & Roese, 2016); the general finding was that the latter are more likely to focus on controllable actions than the former.…”
Section: Structural Envelope Of Counterfactual Thoughtsmentioning
confidence: 99%
“…When thoughts are focused on what might have been, it provides for and facilitates improvement for and of the future, as counter-factual thoughts are archetypally activated by a failed goal, and they specify what might have been done in order to achieve the goal (Dator, 1998). This type of thought generally tends to produce counter-factual thoughts after failure has occurred, rather than after a success and, therefore, counter-factual thinking can be closely related to emotion, social perceptions, and self-understanding (Mercier, et al, 2016). Counter-factuals tend to focus on alternative outcomes that may be perceived as better alternatives to what might be, also known as upward counter-factuals; or as worse than actuality, known as downward counter-factuals.…”
Section: Counter-factual Thinkingmentioning
confidence: 99%
“…CFT has also been linked to future planning (Epstude & Roese, 2008) but compared to future thoughts, it is more likely to focus on uncontrollable events (Ferrante et al 2013;Mercier et al, 2017) and in doing so, may also allow individuals to excuse past failures (Byrne, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Simulating future possibilities plays a key role in planning and goal setting (Epstude et al, 2016) by allowing individuals to consider the consequences of different actions and events. CFT has also been linked to future planning (Epstude & Roese, 2008) but compared with future thoughts, it is more likely to focus on uncontrollable events (Ferrante et al, 2013;Mercier et al, 2017) and in doing so, may also allow individuals to excuse past failures (Byrne, 2016). The CFT that is most functional is that which is self-focused and which concerns how events might have turned out better (termed upward CFT).…”
Section: Introductionmentioning
confidence: 99%